So, my problem is as follows:

$$ U_{xx} +U_{yy}=0; U(x,0)=0, U_x (0,y)=0 ,U_x (L,y)=0 $$

I need to use Separation of Variables, which I did, and got:

$$ U(x,y) = (Ae^{\sqrt{\lambda}x}+Be^{-\sqrt{\lambda}x})(C\cos{\sqrt{\lambda}y}+D\sin{\sqrt{\lambda}y}) $$

for ${\lambda}>0$. My question is how to plug in the boundary conditions, and why this first solution does/doesn't satisfy the conditions.

  • $\begingroup$ You repeat $U_x(0,y)=0$ twice. $\endgroup$ – user17090 Nov 14 '11 at 6:18
  • $\begingroup$ fixed, sorry... $\endgroup$ – Chris Nov 14 '11 at 6:19

You use first $U(x,0)=0$ to get $C=0$ and then use $U_x(0,y)=0$ to get \begin{equation*} (A {\sqrt{\lambda}}e^{\sqrt{\lambda}x}-B \sqrt{\lambda} e^{-\sqrt{\lambda}x})D\cos \sqrt{\lambda}y|_{x=0}=0 \end{equation*} and then $A-B=0$ or $A=B$. Similarily use $U_x(L,y)=0$ to get $A\sqrt{\lambda}[2 sh\sqrt{\lambda} L]=0$ which implies $e^{2\sqrt{\lambda} L}=1$ which gives $\lambda=0$ which is not what you want. So you made an error in choosing the solution. The solution should be: $$U(x,y)=(A\cos \sqrt{\lambda}x +B \sin \sqrt{\lambda}x)(Ce^{\sqrt{\lambda}y} +De^{-\sqrt{\lambda}y}).$$ Now we repeat the above steps to get the values of $A,B,C$ and $D$ (up to a multiplicative factor).

More precisely, plug $U(x,0)=0$ to get $C+D=0$. Then use $U_x(0,y)=0$ to get $\sqrt{\lambda}B=0$ so $B=0$. Also, $U_x(L,y)=0$ implies $\sqrt{\lambda}A\sin \sqrt{\lambda}L =0$ hence $\lambda= \frac{n^2\pi^2}{L^2}$. Finally we put: \begin{equation*} U_n(x,y)= A_n \cos {\frac{n\pi}{L}x} \sinh {\frac{n\pi}{L}y} \end{equation*} which is the required solution and where we absorbed $C$ and $D$ into $A$. The full solution to the problem is of the form \begin{equation*} U(x,y)=\sum_n A_n\cos {\frac{n\pi}{L}x} \sinh {\frac{n\pi}{L}y}. \end{equation*}

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.